The Mediating Role of Patient Satisfaction on the Effect of Physician Competence Quality, Service Quality, and Shared Decision Making on Patient Compliance at Eka Bekasi Hospital - Andry Giovanny; Oscar Jayanagara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Polyclinic services act as the frontline in the health system, providing primary and secondary care to the wider community. However, the quality of services in polyclinics often still does not meet patient expectations. Factors such as doctor quality, service quality and Shared Decision Making are interrelated and contribute directly or indirectly to patient satisfaction. Good service quality in each of these aspects creates a more positive experience for patients and builds trust in health services in polyclinics. Conversely, dissatisfaction with one of these aspects can affect patients' perceptions of overall service quality, which ultimately impacts their level of compliance with medical recommendations.This study aims to analyze the mediating role of patient satisfaction on the influence of doctor competence quality, service quality and shared decision making on patient compliance at Eka Bekasi Hospital. This method uses a quantitative cross-sectional method. Using the Non-Probability Sampling Technique, the sample in this study was 89 respondents.Service Quality affects patient compliance and patient satisfaction. And service quality affects patient compliance which is mediated by patient satisfaction.These findings underscore the importance of focusing on improving service quality in efforts to improve patient satisfaction and compliance, indicating that aspects of the patient experience are more important than individual factors such as physician competence or shared decision-making processes.